2015
DOI: 10.2217/cns.15.29
|View full text |Cite
|
Sign up to set email alerts
|

Seizures in oligodendroglial tumors

Abstract: Epilepsy develops in more than 70-90% of oligodendroglial tumors and represents a favorable indicator for long-term survival if present as the first clinical sign. Presence of IDH1 mutation is frequently associated with seizures in oligodendrogliomas, next to alterations of glutamate and GABA metabolism in the origin of glioma-associated epilepsy. Treatment by surgery or radiotherapy results in seizure freedom in about two-thirds of patients, and chemotherapy to a seizure reduction in about 50%. Symptomatic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 92 publications
2
15
0
1
Order By: Relevance
“…Studies in patients with glioma-induced epilepsy have also shown that the etiology plays an important role in withdrawal success or failure [54][55][56]. Kerkhof et al [24] evaluated the recurrence rate after AED withdrawal in 71 patients with histologically confirmed lowgrade or anaplastic (grades II-III) glioma who were seizure-free for at least 1 year after antitumor treatments, including surgery, radiotherapy, and chemotherapy.…”
Section: Etiologymentioning
confidence: 99%
“…Studies in patients with glioma-induced epilepsy have also shown that the etiology plays an important role in withdrawal success or failure [54][55][56]. Kerkhof et al [24] evaluated the recurrence rate after AED withdrawal in 71 patients with histologically confirmed lowgrade or anaplastic (grades II-III) glioma who were seizure-free for at least 1 year after antitumor treatments, including surgery, radiotherapy, and chemotherapy.…”
Section: Etiologymentioning
confidence: 99%
“…Currently, more and more anti-epilepsy drugs (AEDs), including VPA, phenobarbital, carbamazepine, clonazepam, levetiracetam, lamotrigine, topiramate, and oxcarbazepine, have been concerned in studying tumors of CNS. Among these AEDs, VPA and levetiracetam exhibits superiority in the clinical application of brain tumor-related epilepsy (BTE), due to their sensitization of TMZ through MGMT-dependent or MGMTindependent mechanisms (92,93). In addition, levetiracetam and VPA would be beneficial to verbal memory and cognitive function via downregulating excitatory amino acid transporter-2 expression (94,95).…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed higher OR compared with that study, indicating that glioma patients with oligodendroglioma histology were almost five times more likely to have seizures. This can be explained by the fact that oligodendrogliomas more often involve the cortex; therefore, they are more likely to cause seizures compared with astrocytomas, which tend to be situated in the white matter (Kerkhof et al, 2015;Rudà et al, 2012).…”
Section: Discussionmentioning
confidence: 99%